Probabilistic Model and Solution Algorithm for the Electricity Retailers in the Italian Market - Triki, Chefi; Ghiani, Gianpaolo; Musmanno, Roberto (Algorithmic Operations Research)

(untitled) (Preeminent Academic Facets Inc., 2011)
The paper considers the problem of maximizing the profits of a retailer operating in the Italian electricity market. The problem consists in selecting the contracts portfolio and in defining the bidding strategy in the wholesales market while respecting the technical and regulatory constraints. A novel solution method based on a enhanced discovery of the search domain in the simulated annealing technique has been developed for its solution and a set of realistic test problems have been generated for its validation. The experimental results show that our method outperforms the standard simulated annealing by an improvement gap of 20,48% in average.